Safe Margin beyond Dens Tips to Ventral Dura in Anterior Odontoid Screw Fixation : Analysis of Three-Dimensional Computed Tomography Scan of Odontoid Process - Sung, Min-Jae (J Korean Neurosurg Soc, 2018)
OBJECTIVE: Anterior odontoid screw fixation is a safe and effective method for the treatment of odontoid fractures. The surgical technique is recommended for perforation of the apical cortex of the dens by the lag screw. However, overpenetration of the apical cortex may lead to potentially serious complications such as damages of adjacent vascular and neural structures. The purpose of this study was to assess the role of three-dimensional computed tomography (CT) scan to evaluate the safe margin beyond dens tip to ventral dura for anterior odontoid screw fixation. METHODS: We retrospectively analyzed the three-dimensional CT scans of the cervical spines in 55 consecutive patients at our trauma center. The patients included 38 males and 17 females aged between 22 and 73 years (mean age±standard deviation, 45.8±14.2 years). Using sagittal images of 3-dimensional CT scan, the safe margins beyond dens tip to ventral dura as well as the appropriate screw length were measured. RESULTS: The mean width of the apical dens tip was 9.6±1.1 mm. The mean lengths from the screw entry point to the apical dens tip and posterior end of dens tip were 39.2±2.6 mm and 36.6±2.4 mm. The safe margin beyond apical dens tip to ventral dura was 7.7±1.7 mm. However, the safe margin beyond the posterior end of dens tip to ventral dura was decreased to 2.1±3.2 mm, which was statistically significant (p<0.01). There were no significant differences of safe margins beyond dens tip to ventral dura with patient gender and age. CONCLUSION: Extension by several millimeters beyond the dens tip is safe, if the trajectory of anterior odontoid screw is targeted at the apical dens tip. However, if the trajectory of the screw is targeted to the posterior end of dens tip, extension beyond dens tip may lead to damage immediately adjacent to the vental dura mater.